A multi-scale strategy to predict fretting-fatigue endurance of overhead conductors. (March 2020) - Said, J.; Garcin, S.; Fouvry, S.; Cailletaud, G.; Yang, C.; Hafid, F.
Abstract: Overhead conductors enduring aeolian vibrations are subjected to fretting fatigue damage. To predict the fretting fatigue cracking risk along the conductor-clamp assembly involving a multitude of crossed-strands contacts, a multi-scale analysis is considered. First, a global model provides the spatial distribution of normal, tangential and fatigue loadings for every contact. "Specific" loading cases were simulated using a local FEM model involving a Crossland fatigue stress analysis and a critical distance approach to correct the stress-gradient effects. Mono-contact fretting fatigue experiments were then performed reproducing the exact same loading cases. The comparison between numerical predictions and experimental results showed that a very good prediction of crack-nucleation is achieved using this strategy. However, total failures were not systematically observed. It is believed to be related to the manufacturing process. Wire drawing induces a longitudinal microstructure which promotes cracks with a low diving angle, rather than cracks propagating directly into the bulk. 3D-surface-crack simulations confirm a crack arrest phenomenon induced by the contact-induced compressive stress field. Highlights: Global modeling of a conductor-clamp assembly and assessment of fretting loadings distribution. Local modeling of mono-contact between two aluminium strands to perform crack nucleation predictions. Reverse identification of the optimal distance to use a non-local approach, based on experimental fretting tests. Experimental fretting fatigue tests of a mono-contact subjected to fretting fatigue, comparison with simulations. Stress Intensity Factor calculations to illustrate experimental fretting fatigue results.